Analisis Pengaruh Panjang Pesan terhadap Kualitas Citra pada Steganografi LSB - Andre Ardiansah; Teuku Zakkiansyah; Elandri Gunawan; Muhammad Kharizky Rachman Kombih (JIKUM: Jurnal Ilmu Komputer, 2026)
This study examines how variations in message length influence image quality in Least Significant Bit (LSB) steganography. Steganography embeds secret information into digital images, and LSB is one of the simplest and most widely applied techniques due to its low computational cost and ease of implementation. However, increasing the payload size may degrade the visual quality of the stego-image and make it more susceptible to detection. The objective of this research is to analyze the relationship between the amount of embedded data and the resulting image quality. The method involves embedding messages of different lengths into a set of test images using the LSB approach, followed by quantitative quality assessment through metrics such as Peak Signal-to-Noise Ratio (PSNR) and Mean Squared Error (MSE). Experimental results indicate that longer embedded messages lead to a gradual decline in visual quality, reflected by decreasing PSNR values and increasing MSE scores, although moderate payloads still maintain acceptable image fidelity. These findings highlight the trade-off between capacity and imperceptibility in LSB-based steganography and provide useful guidance for determining suitable message sizes in practical data-hiding applications.